Analisa Model Pembangkit Listrik Tenaga Hibrid Untuk Keberlangsungan Pengering Ikan Teri Nelayan Aceh Besar - Teuku Multazam; Teuku Zulfadli (Fakultas Teknik, 2020)
Anchovies are a group of pelagic fish that inhabit coastal waters and have a very wide distribution. In Indonesia, this species of fish are also preserved through the drying process. The humidity of the drying room must meet the humidity requirements required for drying of 55 - 60%. The natural drying process takes 8 hours of drying time per day for 3 days in areas with high sunshine intensity. Drying work must be accompanied by turning 2-3 times every day. The fish drying technology that has been completed is capable of drying fish for one hour with a capacity of 15 kilograms, and requires a supply of electricity of 3065.5 watts from the state electricity company. The high consumption of electric power required will affect the value of the production costs required so that it is necessary for this analysis to obtain an initial model of the location, type, number of turbines - solar panels, and batteries used to operate the fish dryer. The estimation result of the average daily electric power generated from wind speed is 389,53 watts hour (Wh) and solar energy is 5,79 watt hour. The total potential of electric power generated on period August - September 2020 is 2,31 kilo-watt hour (kWh).